Uji Preferensi Konsumen Terhadap Karakteristik Organoleptik Minuman Sari Kacang Bogor (Vigna subterranea (L) Verdc.) - Sanaya, Dhiyaa; Fitrilia, Tiana; Sarastani, Dewi (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the effect of the ratio of the amount of water on consumer preference on the sensory quality of Bogor bean juice. We employed a Completely Randomized Design (CRD) with one factor and three treatment levels, specifically the addition of 300 mL, 400 mL, and 500 mL of water to 100 grams of Bogor peanut seeds. The analysis performed in this study included sensory quality tests using descriptive methods, consumer acceptance tests with hedonic methods, and chemical quality assessments through proximate analysis of selected Bogor peanut juice drinks. The addition of water to Bogor peanut juice drinks affects consumer preferences regarding color and viscosity, but does not impact their preferences for aroma, taste, or overall assessment. According to the consumer preference tests, the most favored product was the Bogor peanut juice drink made with 400 mL of water. This drink contained 90.45% water, 0.23% ash, 0.21% protein, 1.15% fat, and 8.07% carbohydrates, resulting in an energy value of 43.45 kcal per 100 grams of drink. Bogor peanut juice is being developed as a milk substitute for consumers who are lactose intolerant.